1993
DOI: 10.1172/jci116897
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor-alpha mediates changes in tissue protein turnover in a rat cancer cachexia model.

Abstract: Rats bearing the Yoshida AH-130 ascites hepatoma showed enhanced fractional rates of protein degradation in gastrocnemius muscle, heart, and liver, while fractional synthesis rates were similar to those in non-tumor bearing rats. This hypercatabolic pattern was associated with marked perturbations of the hormonal homeostasis and presence of tumor necrosis factor in the circulation.The daily administration of a goat anti-murine TNF IgG to tumor-bearing rats decreased protein degradation rates in skeletal muscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
157
0
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 280 publications
(173 citation statements)
references
References 39 publications
(36 reference statements)
15
157
0
1
Order By: Relevance
“…As a final remark, tumour necrosis factor (TNF) is an important mediator of cachexia in AH-130 tumour-bearing rats (Costelli et al, 1993;Tessitore et al, 1993a;Llovera et al, 1996) and in other situations. A reported effect of this cytokine, on some cell types at least, is to cause [Ca 2+ ] i elevations (Bick et al, 1997;Furukawa and Mattson, 1998), which, in the light of the present observations, might well have a role in activating the Ca 2+ -dependent proteolysis.…”
Section: Discussionmentioning
confidence: 99%
“…As a final remark, tumour necrosis factor (TNF) is an important mediator of cachexia in AH-130 tumour-bearing rats (Costelli et al, 1993;Tessitore et al, 1993a;Llovera et al, 1996) and in other situations. A reported effect of this cytokine, on some cell types at least, is to cause [Ca 2+ ] i elevations (Bick et al, 1997;Furukawa and Mattson, 1998), which, in the light of the present observations, might well have a role in activating the Ca 2+ -dependent proteolysis.…”
Section: Discussionmentioning
confidence: 99%
“…1,3 Although little is known about the precise mechanism of cachexia, recent studies indicate that inappropriate production and release of cytokines such as tumor necrosis factor-␣ (TNF-␣), interleukin-1 (IL-1), interleukin-6 (IL-6) and interferon-␥, which are secreted from both cancer cells and host tissues, are involved in the induction of cachexia. [4][5][6][7][8] These cytokines have been pos-tulated to cause metabolic changes in the host, associated with enhanced energy requirements for tumor growth, resulting in the loss of adipose and muscle tissues. Blockade of the cytokines by their antibodies reversed the body weight loss and tissue wasting without affecting tumor growth.…”
Section: Introductionmentioning
confidence: 99%
“…As an example, muscle wasting, increased ubiquitin expression and proteasome enzymatic activity are induced in healthy animals by administration of TNF or IL-1 (reviewed in Tisdale, 2008). Consistently, at least in cancer cachexia, many years ago few studies demonstrated the crucial role played by cytokines in the onset of muscle wasting, showing that loss of muscle mass, protein hypercatabolism and ubiquitin hyperexpression could be prevented by treatment of tumor-bearing animals with antibodies directed against IL-6, TNF, or IFN (Matthys et al, 1991;Costelli et al, 1993;Strassmann et al, 1993). Altered cytokine homeostasis, positively correlated with disease progression and mortality rates, was reported also in cancer patients (Attard-Montalto et al, 1998;Nakashima et al, 1998).…”
Section: Inflammationmentioning
confidence: 96%
“…Only few data are actually available about the effectiveness of such kind of drugs in preventing or delaying cancer cachexia. In this regard, anti-TNF antibodies, while not an antagonist of IL-1 receptor, proved effective in reducing anorexia, body weight loss and protein hypercatabolism in tumor-bearing rats (Costelli et al, 1993;Costelli et al, 1995). More recently, a clinical trial performed on advanced cancer patients receiving etanercept showed the lack of any significant improvement of weight loss, anorexia and survival rate (Jatoi et al, 2007).…”
Section: Inhibition Of Cytokine Productionmentioning
confidence: 99%
See 1 more Smart Citation